Obturator hernia as a frequent finding during laparoscopic pelvic exploration: A retrospective observational study. Issue 27 (July 2016) - Susmallian, Sergio; Ponomarenko, Oleg; Barnea, Royi; Paran, Haim
Abstract : Abstract: Hernia through the obturator canal is usually unsuspected and hence undiagnosed. Patients with obturator hernias present as acute cases of intestinal obstruction secondary to strangulation or incarceration, with high rate of morbidity and mortality due to delayed diagnosis and treatment. The know incidence of obturator hernia is low, representing 0.073% (11 of 15, 098) of all hernias repaired at the Mayo Clinic in a retrospective study of 15 years. In this study, we conducted a retrospective analysis of laparoscopic extraperitoneal hernia repairs that were performed between the years 2003 and 2007. All procedures were undertaken by 2 experienced surgeons who performed more than 150 previous surgeries. In 293 patients who underwent repair of bilateral or recurrent inguinal hernia, exploration of the obturator foramen was conducted looking for obturator hernia, which was found in 20 cases (6.82% of patients). The true incidence of obturator hernia is greater than that reported in the literature, and the chances of detecting hernia are greater if an equal number of men and women are scanned could be higher if pelvic scanning was performed.